The Effect of Rational-Emotive Behavior Therapy on Physics Teachers’ Stress Management in Nigeria - Ugwuanyi, Christian (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
This study investigated how rational-emotive behavior therapy (REBT) helped secondary school physics teachers manage work-related stress. There are 86 secondary school physics teachers participated in this study using a randomised control trial group design as the study population. An appropriately validated and trial-tested job stress questionnaire was used to gather data for the study (α=.84). Prior to receiving a 12-week REBT intervention treatment, the participants underwent a pretest. After the intervention ended, the subjects underwent a posttest and were also given a follow-up test two months later. Data generated for this research was analysed analysis of variance (specifically repeated analysis of variance). The outcome of the research revealed that the work stress of the physics teachers exposed to REBT was reduced significantly more than those of the control group. Implications: The research implication is that the work stress of physics teachers can be better managed using the REBT program. The study contributes to advancing the therapeutic space and concern that REBT treatment can be applied.